2022
DOI: 10.1136/bmjopen-2021-052718
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity and associated depression among older adults in India: evidence from a population-based study

Abstract: ObjectiveThe present study aimed to examine the associations of several indicators of food insecurity with depression among older adults in India.DesignA cross-sectional study was conducted using country-representative survey data.Setting and participantsThe present study uses data of the Longitudinal Aging Study in India conducted during 2017–2018. The effective sample size for the present study was 31 464 older adults aged 60 years and above.Primary and secondary outcome measuresThe outcome variable was majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 77 publications
2
12
0
Order By: Relevance
“…Our findings align with previous research indicating higher levels of loneliness among those who are more deprived (Madani et al, 2022) and those who perceive themselves as being less well-off when compared with others (Ayalon, 2019). Our analysis also demonstrated that food security persists as an issue among older Indians who work, with proportions of those reporting food insecurity comparable to those in all over-60s (Muhammad et al, 2022b). Previous research using the LASI data has indicated that measures of food security are associated with measures of depression (Muhammad et al, 2022b;Patel et al, 2022), cognitive function (Kumar et al, 2021), and frailty (Muhammad et al, 2022a) in later life.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings align with previous research indicating higher levels of loneliness among those who are more deprived (Madani et al, 2022) and those who perceive themselves as being less well-off when compared with others (Ayalon, 2019). Our analysis also demonstrated that food security persists as an issue among older Indians who work, with proportions of those reporting food insecurity comparable to those in all over-60s (Muhammad et al, 2022b). Previous research using the LASI data has indicated that measures of food security are associated with measures of depression (Muhammad et al, 2022b;Patel et al, 2022), cognitive function (Kumar et al, 2021), and frailty (Muhammad et al, 2022a) in later life.…”
Section: Discussionsupporting
confidence: 91%
“…Our analysis also demonstrated that food security persists as an issue among older Indians who work, with proportions of those reporting food insecurity comparable to those in all over-60s (Muhammad et al, 2022b). Previous research using the LASI data has indicated that measures of food security are associated with measures of depression (Muhammad et al, 2022b;Patel et al, 2022), cognitive function (Kumar et al, 2021), and frailty (Muhammad et al, 2022a) in later life. In our analysis, we find that a lack of food choice and a lack of food availability, including weight loss due to inadequate food consumption are associated with greater feelings of loneliness among those who work.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Among the studies, six considered older adults to be 50 and above [ 43 , 44 , 46 , 49 51 ]. Four studies focused solely on adults aged 60 and [ 45 , 47 , 48 , 53 ]. In contrast, the rest of the studies included in the review had participants aged 65 and above [ 52 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study used only the latter question for food insecurity [ 43 ]. Two studies used responses to a 5-item questionnaire on food security adapted from the Longitudinal Ageing Study in India survey as their food insecurity outcome [ 45 , 53 ]. The study based in Brazil used the Brazilian Food Insecurity Scale [ 47 ].…”
Section: Resultsmentioning
confidence: 99%